Towards a Strategic Analysis of Water Resources Investments in Kenya : Hydrological, Economic, and Institutional Assessment for Storage Development - World Bank (Washington, DC, 2013)
The objective of this study was to advance the process of prioritizing water storage investments that could reduce water stress in economically important areas. The specific objectives of the study were to (i) outline a comprehensive framework for screening of potential storage sites; (ii) identify important water stressed areas through an updated water balance; (iii) assess alternative multipurpose water storage projects through physical, hydrological and economic criteria; and (iv) analyze institutional and financing aspects of water resources development in Kenya to identify capacity and knowledge inadequacies. The study focused on identifying viable surface water storage projects to increase water supply reliability and mitigate the effects of common multi-year droughts. No new estimates of groundwater resources were made, though they were considered in quantifying overall water availability. The scope of the study was limited to an initial screening of infrastructure options that will increase the reliability of water supply. The state of water service delivery was not assessed as it was outside the scope of this study.